To factor the trinomial \(x^2 + 8x + 12 = 0\), we need to find two numbers that multiply to \(12\) (the constant term) and add to \(8\) (the coefficient of \(x\)). The numbers \(2\) and \(6\) meet these criteria, so we can factor the trinomial as follows:
\[ (x + 2)(x + 6) = 0 \]
Thus, the correct response for Part A is: \[ (x+2)(x+6)=0 \]
Part B
Next, to find the solutions, we can use the zero product property. We set each factor to zero:
- \(x + 2 = 0 \Rightarrow x = -2\)
- \(x + 6 = 0 \Rightarrow x = -6\)
Therefore, the solutions are: \[ x = -2 \quad \text{and} \quad x = -6 \]
So, the correct response for Part B is: \[ x=−2 \text{ and } x=−6 \]